Toxoplasmosis in a pregnant woman - case study - Katarzyna Leszczyńska; Patrycja Ostrogórska-Gonszewska; Dorota Matuszyk (Termedia Publishing House, 2022)
Infection with the protozoan parasite Toxoplasma gondii is a rare health problem among pregnant women, which can pose a serious risk to the foetus. Infections with Toxoplasma gondii in adults are typically asymptomatic. The diagnosis and treatment are important and should be tailored to the clinical status of a pregnant woman and the foetus. The patient management crucially depends on whether the infection was transmitted across the placenta to the foetus. Spiramycin is prescribed when primary maternal toxoplasmosis is diagnosed during gestation until the foetal invasion is confirmed or until delivery. A neonate born to a mother with toxoplasmosis should be diagnosed for congenital toxoplasmosis. Aim of the study was to present the diagnosis, management, and possible complications of toxoplasmosis based on the care of a female patient infected with Toxoplasma gondii. This is a case study. The patient provided informed consent to the observation and access to her medical records. The patient's privacy is protected. This is a case of a 32-year-old pregnant woman hospitalized in the second trimester of pregnancy due to impending preterm delivery. The patient was diagnosed with Toxoplasma gondii infection during hospitalization. Toxoplasmosis may pose a serious threat to the foetus and subsequently to the health of a newborn. If a maternal infection is detected, treatment should be implemented forthwith. A midwife's task is to educate every pregnant woman on the prevention, methods of detection, and treatment of infections with Toxoplasma gondii.